A phase II study of clinical activity of SCH 717454 (robatumumab) in patients with relapsed osteosarcoma and Ewing sarcoma. Issue 10 (30th June 2016) - Anderson, Peter M.; Bielack, Stefan S.; Gorlick, Richard G.; Skubitz, Keith; Daw, Najat C.; Herzog, Cynthia E.; Monge, Odd R.; Lassaletta, Alvaro; Boldrini, Erica; Pápai, Zsuzanna; Rubino, Joseph; Pathiraja, Kumudu; et al.
Abstract: Background: Robatumumab (19D12; MK‐7454 otherwise known as SCH717454) is a fully human antibody that binds to and inhibits insulin‐like growth factor receptor‐1 (IGF‐1R). This multiinstitutional study (P04720) determined the safety and clinical efficacy of robatumumab in three separate patient groups with resectable osteosarcoma metastases (Group 1), unresectable osteosarcoma metastases (Group 2), and Ewing sarcoma metastases (Group 3). Procedure: Robatumumab infusions were administered every 2 weeks and were well tolerated with minimal toxicity. Centrally reviewed response data were available for 144 patients. Results: Low disease burden was important for osteosarcoma response: three of 31 patients had complete response or partial response (PR) by Response Evaluation Criteria in Solid Tumors (RECIST) in resectable patients (Group 1) versus zero of 29 in unresectable patients (Group 2); median overall survival was 20 months in Group 1 versus 8.2 months in Group 2. In centrally reviewed patients with Ewing sarcoma with PET‐CT data (N = 84/115), there were six PR, 23 stable disease, and 55 progression of disease by RECIST at 2 months. Patients with Ewing sarcoma had a median overall survival of 6.9 months. However, responding patients with Ewing sarcoma were allowed to continue on treatment after study closure. A minority of patients with metastatic Ewing sarcoma showed clinical responses and have remained healthy after receiving 25–115 doses of robatumumab with remissions of >4 years duration (N = 6). Conclusions: These findings show that although the IGF‐1R remains an attractive treatment target, additional research is needed to identify responders and/or means to achieve durable remissions in order to successfully exploit IGF‐1R signal blockade in Ewing sarcoma (clinicaltrials.gov: NCT00617890).